Ekstremni vremenski dogodki in amplituda planetarnih valov - Puh, Matjaž (Matrika, 2018)
This paper presents the basics of large-scale atmospheric dynamics, namely Rossby waves propagation in midlatitudes. The quasiresonant amplification of planetary waves theory is summarized and its role in recent extreme weather events is explained, as described by Petoukhov et al. It is a possible dynamical mechanism of stationary waves amplification, which could result in more frequent weather extremes in mid-latitudes.
Keywords: atmosferska fizika; atmospheric physics; ekstremni dogodki; extreme events; meteorologija; meteorology; planetarni valovi; planetary waves; Rossby waves; Rossbyjevi valovi; vreme; weather